METHODS FOR INCREASING THE SERVICE LIFE OF MODERN ASPHALT CONCRETE PAVEMENTS ON HIGHWAYS (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article analyzes methods for increasing the service life of modern asphalt concrete pavements used on highways. The study examines the causes of pavement deterioration, physical and mechanical properties of asphalt concrete, the effectiveness of polymer-modified bitumen, geosynthetic materials, and modern drainage systems. In addition, the advantages of innovative monitoring technologies and environmentally sustainable road construction methods are scientifically substantiated. The research results are important for improving road durability, reducing maintenance costs, and ensuring traffic safety.